Chemical Composition of Native Gold Element from the Gosha Deposit - Guseinov, G.S.; Abasova, Sh.A. (Herald of Azerbaijan Engineering Academy, 2024)
The chemical composition (fineness, impurity elements) of native gold element from this deposit is considered. It has been established that the fineness of gold varies from 650 to 990%, averaging 810%, corresponding to high-grade gold. Impurity elements in the composition of native gold element have also been studied. Their presence in gold is established by special distribution patterns. There is a relatively high cotent of Te (0.02-0.05); Sb (0.06-0.08) and Bi (0.03-0.04). It is explained by the fact that silver under certain conditions, forming compounds with Sb, Bi and Te, falls out of solutions, as a result of which gold becomes high-grade (910-980%).